Experiencing Microaggression: Invisibility, Distress, and Self-Stereotyping Among Northeasterners in India - Sohi, Khushbeen K.; Singh, Purnima (Frontiers in Psychology, 2016)
In the present times, the discrimination experiences of various marginalized groups tend to be characterized by subtle acts of disrespect and intolerance in addition to the traditional and more blatant incidents of violence. One such newer manifestation is microaggression. This research explored the impact of frequency of experiencing invisibility (i.e. feeling ignored or overlooked owing to one’s group membership) on distress among Northeasterners residing in Delhi. Further, the role of individual self-stereotyping as a moderator in the invisibility frequency-distress relationship was investigated. Moderation analysis suggested a significant moderating effect of individual self-stereotyping in the relationship between frequency of experiencing invisibility acts and the distress experienced by Northeasterners. In other words, experiencing invisibility caused distress for participants who saw themselves as prototypical of the Northeasterners. Interestingly, frequency of experiencing invisibility was associated with distress for all Northeasterners, however the size of this relationship was greater for Northeasterners who saw themselves as typical of their group.